ITN Expo 2009 Infrastrutture, telematica e navigazione si incontrano - Pititto, Gianluca (GEOmedia, 2009)
ITN EXPO 2009 From the 15th to the 16th of October the first edition of ITN EXPO: INFRASTRUCTURES, TELEMATICS AND NAVIGATION was held in Turin (Lingotto). ITN 2009 was developed from the combination of two existing events: Infrastructura, an international biennial show dedicated to infrastructural facilities and the conference&expo Telemobility Forum. ITN 2009 offered visitors two days of conferences, informative workshops and seminars of high-level content around the main topics: Infomobility, Infrastructures, Navigation. Workshop conference meetings have been organized with industry managers and public administrators, while thousands of visitors were visiting stands and meeting professionals of the main sectors.